2018
DOI: 10.1097/dcr.0000000000001243
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Metastases in Rectal Neuroendocrine Tumors: Results of a National Cohort Study

Abstract: BACKGROUND: Rectal neuroendocrine tumors are often found incidentally. Local excision alone has been advocated for lesions ≤2 cm; however, the evidence base for this approach is limited. OBJECTIVE: Associations among tumor size, degree of differentiation, and presence of distant metastatic disease were examined. DESIGN: This was a retrospective cohort study. SETTINGS: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 22 publications
3
23
1
Order By: Relevance
“…For rectal neuroendocrine tumors, resection is routinely recommended for all tumors, but the type of resection depends predominantly on tumor size given its previously established concordance with lymph node status which has historically been shown to predict worse tumor biology. [1][2][3][4][5] Consequently, successful staging and selection for type of resection for rectal neuroendocrine tumors relies on preoperative identification of lymph node involvement. However, accurate preoperative evaluation of lymph node status remains difficult in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…For rectal neuroendocrine tumors, resection is routinely recommended for all tumors, but the type of resection depends predominantly on tumor size given its previously established concordance with lymph node status which has historically been shown to predict worse tumor biology. [1][2][3][4][5] Consequently, successful staging and selection for type of resection for rectal neuroendocrine tumors relies on preoperative identification of lymph node involvement. However, accurate preoperative evaluation of lymph node status remains difficult in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have advocated for RR for any tumour >10 mm due to the increased risk for lymph node (LN) and distant organ metastasis. [10][11][12][13] However, in our matched comparison of patients with tumours 10-20 mm, we found no difference in OS between LE and RR. Most guidelines recommend RR (e.g.…”
Section: Discussionmentioning
confidence: 60%
“…3,[5][6][7] Using tumour size as a criterion, some studies have suggested that local excision (LE) is sufficient for patients with tumours <2 cm, 8,9 while others recommend radical resection (RR) for all tumours >1 cm. [10][11][12][13] In addition, in a nationwide analysis of patients with rNET, 11.7% of patients underwent biopsy alone, leading the authors to suggest that observation alone is sufficient for tumours <1 cm 4 . Based on previous studies, national guidelines for the treatment of rNET are also largely stratified by tumour size, with LE recommended for tumours <2 cm and RR (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the above, we can infer that that controversy regarding endoscopic or surgical resection focuses on the tumor size and lymph node metastases rather than critical factors associated with recurrence . In our study, we performed multivariate analyses to identify the different risk factors contributing to lymph node and distant metastases.…”
Section: Discussionmentioning
confidence: 96%